Variability of the Horizontal Geomagnetic Field at High-Latitude during Sunspot Maximum - Devi, Rajni; Shailendra, Saini; Dhar, Ajay; Gwal, A.K. (My University, 2017)
In this paper we study the horizontal component of the Earth’s magnetic field and the effect of solar features on geospheric conditions is carried out and carried out at the Indian Antarctic Station “MAITRI”(geom. Lat. 62S, Long. 52.8E), during sunspot maximum activity (2003-2004). The results of the analysis carried out revealed that the amplitude of H has diurnal variation which peaks during the evening and night time while minimum is seen during daytime. Variability is higher during equinox (2003) and summer (2004).The equinoctial maximum is due to enhanced subauroral zone electron density at equinox. From a correlative study of variability in H with possible causative factor such as sunspot activity, magnetic activity and solar activity, it is seen that the magnetic activity has appreciable association with the variability of H. We have also compared the variability during quiet, disturbed days and daily disturbances. No distinct association between disturbed days and daily disturbances is observed. It is observed that maximum number of GMSs have occurred during the maximum solar activity years 2003 than 2004 of 23rd solar cycles.
Keywords: Horizontal component; Magnetic activity; Magnetospheric interactions; Solar flare; Coronal mass ejection; Geomagnetic storm; Sunspot numbers; Solar flux